Incorporation of developing country perspective in World Organisation for Animal Health (OIE) guidelines on prioritization of animal diseases for which vaccines could reduce antimicrobial use - CGIAR Research Program on Livestock (2018)
The World Organisation for Animal Health (OIE) is a key institution for global veterinary policy and its outputs help regulate international trade of livestock and livestock products. The guideline was developed in support of the Global Action Plan on antimicrobial resistance (AMR) and helps to identify where private and public sector vaccine research and development activities should focus. ILRI's participation drew attention to developing country issues such as key diseases, challenges for vaccine uptake and the importance of delivery systems.